DESIGN OF DIGITAL-TO-ANALOG CONVERTER FOR WIMAX TRANSMITTER - PRAYUDI (NIM 13205078), IMAN
In this final year project, a 160MHz 12bit current steering DAC for WiMAX subscriber's transmitter has been designed in a 0.35um SiGe BiCMOS process. Overall, the DAC consists of two parts, i.e. digital part, which is made by the ideal logic gates that are available on SIMetrix simulator, and analog part. To minimize glitch energy, the design is based on 4+8 segmented architecture. To achieve high linearity, a single cascode current source is used. The size of all PMOS transistors, except the current source transistors, is adjusted to obtain the optimal performance. The minimum size of the current source transistors are determined by random mismatch calculation. The performance of the DAC is verified by transistor-level simulation which the result proves that the DAC achieves up to 34.8dB SFDR in the interval from dc to nyquist frequency.